Linking habitat and population viability analysis models to account for vegetation dynamics, habitat fragmentation, and social behavior of a metapopulation of Florida scrub-jays - Lacy, Robert C.; Breininger, David R.; Breininger, Daniel J.; Savage, Anna E.; Forsman, Anna M.; Hoffman, Eric A.; McGuffey, Stephen D.; DeMeyer, David; Mecklenborg, Todd (Frontiers in Conservation Science, 2024)
Population dynamics and viability are driven by interactions among habitat and species biology. The Florida scrub-jay (Aphelocoma coerulescens) is a declining and Federally Threatened bird species that requires mid-succession habitat of partly open soil surface with mid-height vegetation. This habitat is created and sustained in a dynamic state of vegetation growth and periodic natural (e.g., fire) or managed (e.g., mechanical clearing) disturbances. Florida scrub-jays once occupied open oak scrub habitats across much of peninsular Florida but have been reduced to a few regional metapopulations and scattered isolated remnant populations. Many of these populations are undergoing continuing decline as open scrub is either converted to residential development or transitions into closed pine and oak forests due to fire suppression. Long-term field studies have shown that breeding and survival rates are determined by the quality of the scrub habitat, with the demography influenced by and in turn mediating the social structure. Prior Population Viability Analyses (PVA) that included dependencies of demographic rates on habitat and social structure indicated that the east coast Florida metapopulations were fragmented into remnant protected patches that were too small and isolated to support long-term persistence, even if the remaining habitat area and quality was sustained. Moreover, recent modeling of habitat transitions under various proposed management schemes, in conjunction with implementation of Adaptive Resource Management (ARM), projected that the proportion of optimal habitat will continue to decline. In this study, we integrated these habitat projections within the PVA and found that the Brevard County mainland metapopulation is projected to decline toward extinction unless habitat quality, extent, and connectivity can be improved. Land managers have recently implemented new innovative methods for restoring optimal scrub habitat, identifying potential improvements in habitat connectivity of nearby populations, and translocation methods to increase and reinforce the demographic and genetic integrity of local populations. Our linked habitat-population models project that the combination of such habitat and population management actions can stabilize the metapopulation and achieve long-term viability.